Wear failure of a leaded bronze bearing: correlation between plant experience and laboratory wear test data - Ahsan, Q.; Haseeb, A.S. Md. Abdul; Haque, E.; Celis, Jean Pierre (Springer Verlag (Germany), 2003)
This paper describes an investigation on the failure of a large leaded bronze bearing that supports a nine-ton roller of a plastic calendering machine. At the end of the normal service life of a good bearing, which lasted for seven years, a new bearing was installed. However the new one failed catastrophically within a few days, generating a huge amount of metallic wear debris and causing pitting on the surface of the cast iron roller. Following the failure, samples were collected from both good and failed bearings. The samples were analyzed chemically and their microstructures examined. Both samples were subjected to accelerated wear tests in a laboratory type pin-on-disk apparatus. During the tests, the bearing materials acted as pins, which were pressed against a rotating cast iron disk. The wear behaviors of both bearing materials were studied using weight loss measurement. The worn surfaces of samples and the wear debris were examined by light optical microscope, scanning electron microscope, and energy-dispersive x-ray microanalyzer. It was found that the laboratory pin-on-disk wear data correlated well with the plant experience. It is suggested that the higher lead content (similar to18) of the good bearing compared with 7 lead of the failed bearing helped to establish a protective transfer layer on the worn surface. This transfer layer reduced metal-to-metal contact between the bearing and the roller and resulted in a lower wear rate. The lower lead content of the failed bearing does not allow the establishment of a well-protected transfer layer and leads to rapid wear.